What is Federated Learning in Healthcare? Unlocking AI's Potential While Protecting Patient Data - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The promise of Artificial Intelligence AI and Machine Learning ML to revolutionize healthcare is immense. However, this potential is fundamentally constraine...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care